Model Tata Kelola Zakat Produktif Holistik Berbasis Good Community Engagement - Abdul Wasik; Irma Nurhayati (Economia: Journal of Economics and Management, 2026)
Productive zakat is a strategic instrument for transformative and long-term economic empowerment, requiring governance grounded in transparency, participation, and sustainability. Kampung Zakat BAZNAS Bondowoso and Kampung SDGs BAZNAS Jember illustrate community-based zakat practices; however, a systematic and contextual governance model is still needed to support the transformation of mustahik into muzakki and to strengthen the Ber-ISI values—intellectuality, spirituality, and integrity. This study aims to develop a holistic productive zakat governance model based on Good Community Engagement (GCE) to enhance the effectiveness of zakat distribution and community empowerment. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation analysis. The study examines five core GCE pillars: participation, accountability, transparency, inclusivity, and sustainability. The findings demonstrate that integrating GCE principles with a holistic productive zakat approach produces governance that is not only efficient and effective but also empowers communities economically, socially, intellectually, and spiritually. This model offers a policy framework for zakat management that is community-rooted rather than solely institution-centered. Abstrak Zakat produktif merupakan instrumen strategis dalam pemberdayaan ekonomi umat yang berorientasi transformasi jangka panjang, sehingga menuntut tata kelola yang transparan, partisipatif, dan berkelanjutan. Kampung Zakat BAZNAS Bondowoso dan Kampung SDGs BAZNAS Jember merepresentasikan praktik zakat berbasis komunitas, namun masih memerlukan model tata kelola yang sistematis dan kontekstual untuk mendorong transformasi mustahik menjadi muzaki serta penguatan kualitas Ber-ISI (intelektualitas, spiritualitas, dan integritas). Penelitian ini bertujuan mengembangkan model tata kelola zakat produktif holistik berbasis Good Community Engagement (GCE) guna meningkatkan efektivitas distribusi zakat dan pemberdayaan mustahik. Penelitian menggunakan pendekatan kualitatif dengan studi kasus melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi. Analisis data dilakukan secara tematik dengan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa integrasi prinsip GCE—partisipasi, akuntabilitas, transparansi, inklusivitas, dan keberlanjutan—dengan pendekatan zakat produktif holistik membentuk tata kelola yang efektif, efisien, dan berorientasi pada pemberdayaan ekonomi, sosial, spiritual, dan intelektual masyarakat. Model ini menawarkan formulasi kebijakan pengelolaan zakat yang berakar pada kekuatan komunitas lokal, bukan semata pendekatan kelembagaan.